1998
DOI: 10.1017/s135583829800106x
|View full text |Cite
|
Sign up to set email alerts
|

T7 RNA polymerase produces 5′ end heterogeneity during in vitro transcription from certain templates

Abstract: The use of T7 RNA polymerase to prepare large quantities of RNA of a particular sequence has greatly facilitated the study of both the structure and function of RNA. Generally, it has been believed that the products of this technique are highly homogeneous in sequence, with only a few noted exceptions. We have carefully examined the transcriptional products of several tRNAs that vary in their 59 end sequence and found that, for those molecules that begin with multiple, consecutive guanosines, the transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(92 citation statements)
references
References 23 publications
(15 reference statements)
2
90
0
Order By: Relevance
“…A GCG sequence was added at the beginning of the transcript to minimize the 5Ј heterogeneity of the RNA population (29). Transcription and RNA purifications steps were performed as described previously (30).…”
Section: Methodsmentioning
confidence: 99%
“…A GCG sequence was added at the beginning of the transcript to minimize the 5Ј heterogeneity of the RNA population (29). Transcription and RNA purifications steps were performed as described previously (30).…”
Section: Methodsmentioning
confidence: 99%
“…The biggest limitation to preparing tRNA by in vitro transcription is that the products frequently possess 3′ and/or 5′ sequence heterogeneities [20,25,26]. These must be eliminated by either tedious purification at reduced yields, or by use of ribozyme sequences to excise the full-length tRNA from flanking regions [27,28].…”
Section: Preparation Of Trna For Kinetic Studiesmentioning
confidence: 99%
“…For the aminoacyl transfer reaction pathway, the relative standard free energies can be calculated relative to the standard free energy of the E•AA~AMP intermediate using the following equations: (26) (27) The Gibbs activation energy for each reaction can be calculated by subtracting the standard free energy for the enzyme complex preceding the transition state from that of the transition state. All free energies are calculated assuming a standard state of 1 M ATP, 1 M amino acid, and 1 M pyrophosphate.…”
Section: Calculation Of Relative Standard Free Energiesmentioning
confidence: 99%
“…Such a mechanism has been proposed to explain the 5Ј end heterogeneity of RNA transcripts produced by the DNA-dependent RNA polymerases of E. coli and T7 bacteriophage (39)(40)(41). However, the templates in those studies contained homooligomeric nucleotides not found on the satC templates truncated by 3 or 4 bases.…”
Section: In Vitro Synthesis Of Satc By the Tcv Rdrp Using Templates Cmentioning
confidence: 99%